Intrigues of Accessing Mental Health Services Among Urban Refugees Living in Kenya: The Case of Somali Refugees Living in Eastleigh, Nairobi. Issue 2 (3rd April 2019) - Mutiso, Victoria; Warsame, Abdulkadir Hussein; Bosire, Edna; Musyimi, Christine; Musau, Abednego; Isse, Maimuna Mohamud; Ndetei, David M.
ABSTRACT: This article explores the perceived mental-health-care access barriers affecting the resettled refugee population in Eastleigh, Kenya. Findings suggest that the main barriers to accessing mental health care are cultural and religious beliefs, inadequate health services, culture-insensitive mental health services, poverty, language barriers, stigma, and discrimination. This study recommends that it is important to integrate Somalis' indigenous methods of treatment of mental illnesses into Western methods of treatment in Kenya to provide a wide spectrum of mental help to refugees.